Application of kinetic model of adsorption for Elovich and the intraparticles diffusion, the Sticking probability (S*), Tempkin isotherm on some different aromatic and aliphatic acids - Khaleel Al-Niemi (College of Education for Pure Sciences, 2019)
This study is including application of the kinetic model of Elovich equation to calculate the initial rate of adsorption (α) and desorption constant (β), Tempkin constant (BT) which refer to the relation with surface capacity of adsorped solid, the potential sticking probability (S*) and apparent activation energy was determined which indicate that of lower temperature of solution favorite the removal by adsorption. The values of (S*) less than one this indicates that the sticking is favorite and physical mechanism predominate. The initial rate constant of intraparticles diffusion was calculated. these studies applied on some amino acids, aliphatic and aromatic dicarboxylic acids as well as α- hydroxyl acids, and aromatic acids.   (Key words): Kinetic model , Elovich , Intraparticles , Sticking probability , Tempkin isotherm , Aromatic and aliphatic.